A Dynein Light Intermediate Chain, D1bLIC, Is Required for Retrograde Intraflagellar Transport - Hou, Yuqing (The American Society for Cell Biology, 2004)
Intraflagellar transport (IFT), the bidirectional movement of particles along flagella, is essential for flagellar assembly. The motor for retrograde IFT in Chlamydomonas is cytoplasmic dynein 1b, which contains the dynein heavy chain DHC1b and the light intermediate chain (LIC) D1bLIC. To investigate a possible role for the LIC in IFT, we identified a d1blic mutant. DHC1b is reduced in the mutant, indicating that D1bLIC is important for stabilizing dynein 1b. The mutant has variable length flagella that accumulate IFT-particle proteins, indicative of a defect in retrograde IFT. Interestingly, the remaining DHC1b is normally distributed in the mutant flagella, strongly suggesting that the defect is in binding of cargo to the retrograde motor rather than in motor activity per se. Cell growth and Golgi apparatus localization and morphology are normal in the mutant, indicating that D1bLIC is involved mainly in retrograde IFT. Like mammalian LICs, D1bLIC has a phosphate-binding domain (P-loop) at its N-terminus. To investigate the function of this conserved domain, d1blic mutant cells were transformed with constructs designed to express D1bLIC proteins with mutated P-loops. The constructs rescued the mutant cells to a wild-type phenotype, indicating that the function of D1bLIC in IFT is independent of its P-loop.